Experimental Study of an Aluminum-Polysilicon Thermopile for Implementation of Airflow Sensor on Silicon Chip - Subandi, Ayub; Idris, Irman; Ahmad, Adang Suwandi (Journal of Engineering and Technological Sciences, 2007)
A multi-directional airflow sensor has been realized. The essential part ofÂ  theÂ  consideredÂ  sensorÂ  isÂ  aÂ  thermopileÂ  configuration,Â  whichÂ  enablesÂ  the measurementÂ  ofÂ  flowÂ  speedÂ  andÂ  flowÂ  direction.Â  TheÂ  thermopileÂ  isÂ  aÂ  series arrangementÂ  ofÂ  eightÂ  thermocouples.Â  AÂ  thermocoupleÂ  convertsÂ  aÂ  differenceÂ  in temperatureÂ  intoÂ  anÂ  electricalÂ  signal,Â  byÂ  meansÂ  ofÂ  theÂ  SeebeckÂ  effect .Â  The thermocouplesÂ  areÂ  madeÂ  ofÂ  aluminum-N-typeÂ  polysiliconÂ  junctions.Â  The incomingÂ  flowÂ  isÂ  heatedÂ  andÂ  theÂ  degreeÂ  ofÂ  heatÂ  transferÂ  byÂ  convectionÂ  toÂ  the flow, depends on the speed of the flow; the faster the flow the smaller the heat transfer,Â  which leads to a smaller (Seebeck) outputÂ  voltage ofÂ  the thermopiles. AfterÂ  signalÂ  conditioningÂ  -Â  i.e.,Â  filteringÂ  andÂ  amplificationÂ  byÂ  meansÂ  ofÂ  an amplification systemÂ  -Â  the electrical output signals of the thermopiles are further signal-processed by applying analog-to-digital signal conversion, so that finally the flow speed and the flow direction can be properly displayed on a computer screen. The measured values of the Seebeck coefficient or thermopower (S) were in the range of: 0.43 to 0.68 mV/K which are in good agreement with the values found in the literature: 0.5 to 0.7 mV/K. Moreover, itÂ  was found that theÂ  flow speedÂ  Uï¥ isÂ  proportionalÂ  toÂ  theÂ  reciprocalÂ  valueÂ  ofÂ  theÂ  squareÂ  ofÂ  theÂ  output voltage of the outgoing thermopile.